Diabetic lower extremity complications, fear of falling and associated HbA1c levels: A cross-sectional study of the East Harlem population. Issue 4 (October 2016) - Shtofmakher, Garry; Kilfoil, Roger L.; Rozenstrauch, Adam; Rothstein, Michael; Weintraub, Matthew
Highlights: Early detection of lower extremity complications from diabetes could reduce the high healthcare cost associated with their treatment. Fear of falling has a negative impact on patients' quality of life and well being. No correlation between HbA1c and the number of podiatric manifestations was found in our study. HbA1c is a poor predictor of the number of podiatric manifestations. There is no indication that fear of falling is associated with the number of podiatric manifestations. Patients on Neuropathy drugs reported lower MFES scores, and have an increased risk/fear of falling Abstract: The primary aim of this study was to determine if HbA1c is a positive predictor of the lower extremity complications commonly manifested in diabetes. A secondary objective was to investigate if the progression of diabetes-related complications had any affect on the fear of falling. This was a study of 38 patients enrolled at the Foot Center of New York. Prospective subjects were recruited if they reported an International Classification of Diseases (ICD) code consistent with diabetes using electronic medical records, expressed a desire to participate, conformed with the inclusion and exclusion criteria for the study (they were over 18 years of age and considered alert and thereby able to consent to the study), and provided informed consent. A total of 38 patients were enrolled in the study. Most of the participants were male and African American. The mean number of podiatric manifestations in the group was 4.43 (SD = 62.35). The mean HbA1c level for the group was 8.23% (SD = 1.94). Several predictors of podiatric manifestations were examined in the study, including mean MFES (Modified Falls Efficiency Scale) score, age, concurrent treatments for neuropathy, and HbA1c levels. Simple correlational analyses revealed that there was no correlation between HbA1c and the number of podiatric manifestations. Several follow-up regression analyses were performed to assess the ability of HbA1c to predict podiatric manifestations when controlling for individual parameters such age and duration of diabetes. HbA1c did not predict number of podiatric manifestations after controlling for age and diabetes duration, age alone or diabetes duration alone. The study did find that patients receiving neuropathy drugs reported lower MFES scores (notably, lower MFES scores are associated with a higher risk of falling). HbA1c levels of patients receiving neuropathy drugs did not differ significantly from the HbA1c levels of patients not receiving neuropathy drugs. The podiatric manifestations of patients with diabetes in East Harlem, where this study was carried out, are wide-ranging and include nail and skin disorders, which are both recognized as common precursors to infections and amputations. Predictive tools could help reduce the economic burden of diabetes. This study assessed the ability of HbA1c to predict the total number of podiatric manifestations in diabetic patients. In the end, HbA1c was not a good predictor of the number of podiatric manifestations. The weak correlation between HbA1c levels and the total number of podiatric manifestations in this study might be due to the small sample size. Future studies, ideally involving a larger sample size, are needed to more accurately assess the potential of HbA1c for predicting lower extremity complications.